Nitrogen fertilizer and faba bean density as sources of nitrogen supply in sustainable production of forage corn - Samaneh Ghorbi; Ali Ebadi; Saeid Khomari; Masoud Hashemi (پژوهش‌های حبوبات ایران)
IntroductionSome studies have reported that application of chemical fertilizers, especially nitrogen, is one of the most appropriate methods to increase crop production and maintain food security in the world. However, it should also be noted that the improper use of nitrogen fertilizers can disrupt natural ecosystems. Alternative methods can be used to prevent this, such as the use of plants with biological nitrogen fixation (e.g., legumes). Faba bean is one of the most important varieties of this family (Fabaceae) and contains 24-30% protein and 51-68% carbohydrates. This plant is one of the most important spices of the genus (Vicia) and has a high yield compared to other legumes. Due to its environmental, economic and agroecological performance, faba bean can improve the sustainability of agricultural ecosystems. Corn (Zea mays L.) is one of the most important annual cereals. However, maize cultivation is not economical because it requires nitrogen fertilizer, and improper use of nitrogen also increases ecosystem instability. Incorporating legumes into cropping systems is critical for sustainable management of agricultural systems and reducing nitrogen fertilizer requirements for corn production. Materials and MethodsA two-year experiment was conducted in 2018-2019 as a factorial experiment based on a randomized complete block design with three replications at the research farm of the Faculty of Agriculture and Natural Resources, university of Mohaghegh Ardabili, Ardabil, Iran. The experimental treatments were different plant densities of faba bean (25, 35, 40 and 80 plants m-2) and different nitrogen fertilizer rates (0, 100, 200 and 300 kg ha-1) of forage corn. In this experiment, the faba bean variety Shadan was planted and manually harvested at the physiological maturity stage. The corn variety was a single cross hybrid 201, which was planted at a density of 80000 plants ha-1 in the rows with faba bean residues. At the V5 stage of corn, N fertilizer (as urea) was applied in 3 stages. Three corn plants were harvested at the milk stage and then oven dried at 70°C for 72 h and weighed. Traits studied in this experiment included chlorophyll index, plant height, root nodule dry weight, root dry weight, number of root nodules, and grain yield in faba bean, and chlorophyll index, protein harvest index, plant height, number of leaves per plant, physiological nitrogen efficiency, nitrogen uptake efficiency, and dry matter yield in forage corn. Statistical analysis of data was performed using SAS 9.4 software, and significant differences between treatment means were tested using the Duncan's Multiple Range Test at P< 0.05. Results and DiscussionFaba beanThe highest grain yield (g m-2), plant height (cm) and chlorophyll index of faba bean were obtained at the density of 80 plant m-2. At the densities of 25 and 35 plants m-2, the number of root nodules and the dry weight of root nodules (g) were the highest. As plant density increased, root dry weight (g m-2) also increased, so that the density of 80 plants m-2 had the highest root dry weight per m2. The highest fertility rate was observed at the densities of 80 and 40 plants m-2.CornOur results showed that the interaction between faba bean density and N fertilizer had effects on plant height, chlorophyll index, protein harvest index, physiological nitrogen efficiency, nitrogen uptake efficiency, and dry forage yield. The results of the mean comparisons showed that the highest dry forage yield was obtained at the density of 40 faba bean plants+200 kg N ha-1 an increase of 155% over the control treatment. The highest number of leaves was observed in the treatments at the density of 40 faba bean plants+100 kg N ha-1, at the density of 40 faba bean plants+200 kg N ha-1 and at the density of 35 faba bean plants+200 kg N ha-1. The density of 40 plant of faba bean+100 kg N ha-1 and the density of 40 plant of faba bean+200 kg N ha-1 had the highest plant height. The highest chlorophyll index was obtained at the the density of 40 faba bean plants+200 kg N ha-1. Finally, the results showed that employment of faba bean in rotation and non-application of nitrogen fertilizer increased nitrogen uptake efficiency of forage corn. ConclusionComparison of the different treatments showed that the density of 40 plants of faba bean and 200 kg N ha-1 was superior in most of the evaluated traits. Overall, the results suggest that the use of faba bean in crop rotation is an appropriate approach to reduce the use of chemical fertilizers in agricultural systems, according to the results, the use of the density of 40 plants of faba bean and 200 kg N ha-1 were recommended under the same weather conditions.